Can tourism lead competitive and sustainable development now and in the near future in Colombia? - Leonardo Garavito; Edna Rozo; Francisco Mojica (Via@)
This text presents a synthesis of the main results of a research project called “2030: a vision of tourism in Colombia”, whose central objective was to make a comprehensive assessment of tourism and to contribute guidelines and critical reflections on Colombia’s tourism policy and development. A major challenge was identified: how to achieve tourism while at the same time reducing social inequity and improving quality of life for the host communities of the zones that concurrently have the highest levels of environmental biodiversity and culture, and of poverty. If tourism in Colombia continues on its recent development pathway that is stimulated by external and unplanned factors, unsustainable scenarios are highly likely to emerge.